A comparative study on the anti-bacterial effect of the different permanent endodontic sealers used during obturation - Virata, Vivian Chan
This study was undertaken to determine the anti-bacterial effect of various endodontic permanent sealers which are : Apexit, Endomethasone, Sealapex, Tubliseal, Zial, and Zinc Oxide Eugenol, against four selected anaerobic bacteria,namely Bacteroides Corrodens, Lactobacillus species, Peptostreptococ-cus Anaerobius, Veilonella Parvula. The experiment involved the testing of the six sealers using the tube dilution method with thioglycolate broth and the bacteria without any sealer were used as controls. Inhibitions of bacterial growth was recorded for each test tube and the results were analyzed statistically to compare the anti-bacterial effects of the sealers.